Geodatabase Development for Visualizing Obesity Risk Factors in New Mexico–Mexico Border Communities. (3rd April 2019) - Campbell, Carol L.; McDonald, Jill A.; Sroka, Christopher J.; Guerrero, Arthur D.; Olivares, Elizabeth; Sharkey, Joseph R.
Abstract: Geospatial techniques can assist community health scientists developing interventions to promote physical activity and healthy lifestyles in border communities, yet collaboration with geographers is underutilized. As part of a project to prevent child obesity in three southern New Mexico communities, a geodatabase was developed to accommodate survey data that included fifty-eight street and neighborhood characteristics of 949 street segments in sixteen clusters of households. Geographic locations for these street segments and community assets, such as parks, were included. Distributions of street segment characteristics and community assets were compared across clusters, and similar groups of clusters were identified using principal component analysis and hierarchical cluster analysis. The geodatabase facilitated visualization of spatial relationships between community assets and patterns of street segment characteristics that would inform decisions about interventions that encourage outdoor physical activity and healthy habits. Collaboration between scientists in geography and public health has untapped potential in addressing community health disparities.